Desired features and facets of a digital technology tool for the self-management of wellbeing in a non-clinical sample of young people - Babbage, Camilla; Jackson, Georgina; Nixon, Elena (JMIR Publications, 2018)
Background: Adaptive coping behaviours can improve wellbeing for young people experiencing life stressors while maladaptive coping can increase vulnerability to mental health problems in youth and into adulthood. Young people could potentially benefit from the use of digital technology tools if the latter could help enhance their coping skills and overcome barriers in help-seeking behaviours. However, little is known about the desired digital technology use for self-management of wellbeing among young people in the general population. Objective: This was a small, qualitative study aimed at looking into what young people desire from digital technology tools for the self-management of their wellbeing. Methods: Young people aged 12 to 18 were recruited from the general community to take part in semi-structured interviews. Recorded data from the interviews were transcribed and analysed using inductive thematic analysis. Results: Fourteen participants were recruited and completed the study, with a mean age of 14.6 (3/14 female). None of the participants reported using any digital tools specifically designed to manage wellbeing. However, as indicated through the emerged themes, young people used digital technology to reduce their stress levels and manage their mood, mainly through games, music and videos. Overall, identified themes denoted that young people were keen on using such tools and desired certain facets and features of an ideal tool for the self-management of wellbeing. Themes relative to the facets indicated what young people felt a tool should do to improve wellbeing, including being immersed into a stress-free environment, being uplifting and such a tool would direct them to resources based on their needs. The feature-based themes suggested that young people wanted the tool to be flexible and to enable engagement with others whilst also being sensitive to privacy. Conclusions: The young people interviewed in this study did not report engaging with digital technology specialised to improve wellbeing but instead used media already accessed in their daily lives in order to self-manage their psychological states. As a result, the variety of coping strategies reported and digital tools used was limited to the resources that were already being used for recreational and social purposes. The present findings contribute to the scarce research into young people’s preferred use of digital technology tools for the self-management of their wellbeing. However, this was a small-scale study and the current participant sample is not representative of the general youth population therefore the results are only tentative and warrant further investigation.